Effect of ABCB1 SNP polymorphisms on the plasma concentrations and clinical outcomes of rivaroxaban in Chinese NVAF patients: a population pharmacokinetic-based study - Wang, Fei; Li, Ze; Huang, Youqi; Liu, Qin; Zhao, Libin; Wang, Honghong; Gao, Hongjin; Chen, Mingyu; Lin, Yuze; Li, Xingang; Chen, Min (Frontiers in Pharmacology, 2025)
BackgroundThis study utilized a population pharmacokinetic (PPK) approach to assess the influence of ABCB1 genetic polymorphisms on the plasma concentrations and clinical outcomes of rivaroxaban.MethodsThe PPK model for rivaroxaban was developed using the nonlinear mixed-effects modelling approach and Monte Carlo simulations were employed to derive peak concentration (Cmax) and trough concentration (Ctrough). ABCB1 genetic variants were analyzed for their impact on the plasma concentrations and clinical outcomes.ResultsAnalysis of 287 rivaroxaban plasma concentrations from 228 non-valvular atrial fibrillation (NVAF) patients revealed significant associations between AST (aspartate aminotransferase)/ALT (alanine aminotransferase) ratios and the apparent clearance (CL/F), the apparent volume of distribution (V/F). ABCB1 1236C>T TT and ABCB1 c.2482-2236C>T CC genotypes exhibited higher dose-adjusted Cmax (Cmax/D) compared to other relevant genotypes. Additionally, the ABCB1 3435C>T TT genotype showed lower dose-adjusted Ctrough (Ctrough/D) compared to CC or CT genotypes. For clinical outcomes, the ABCB1 c.2482–2236C>T CC genotype had a higher bleeding risk compared to TT (RR = 1.99, 95% CI 1.08–3.69) or CT genotypes (RR = 1.42, 95% CI 1.04–1.92), and ABCB1 3435C>T TT genotype showed a higher thromboembolic risk compared to CC genotype (RR = 3.48, 95% CI 1.02–11.85).ConclusionThe PPK model incorporated CL/F and V/F with the covariate AST/ALT. Model-based simulations revealed that ABCB1 1236C>T, ABCB1 c.2482–2236C>T, and ABCB1 3435C>T genotypes had significant impacts on the plasma concentrations of rivaroxaban. Specifically, ABCB1 c.2482-2236C>T and ABCB1 3435C>T genotypes were associated with bleeding events and thromboembolic events, respectively.